2014
DOI: 10.1016/j.jare.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of heat transfer and thermal performance with longitudinal fins of solar air heater

Abstract: The thermal performance of a single pass solar air heater with five fins attached was investigated experimentally. Longitudinal fins were used inferior the absorber plate to increase the heat exchange and render the flow fluid in the channel uniform. The effect of mass flow rate of air on the outlet temperature, the heat transfer in the thickness of the solar collector, and the thermal efficiency were studied. Experiments were performed for two air mass flow rates of 0.012 and 0.016 kg s−1. Moreover, the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…Different shapes of fins have been studied. First, longitudinal fins which was studied by many researchers either experimentally [6][7][8] or theoretically [9,10]. The results of such studies confirmed that attaching fins to the absorber plate improves the performance of SAH as they have higher heat transfer area and lower irreversibility compared to flat plate SAH.…”
Section: Introductionmentioning
confidence: 86%
“…Different shapes of fins have been studied. First, longitudinal fins which was studied by many researchers either experimentally [6][7][8] or theoretically [9,10]. The results of such studies confirmed that attaching fins to the absorber plate improves the performance of SAH as they have higher heat transfer area and lower irreversibility compared to flat plate SAH.…”
Section: Introductionmentioning
confidence: 86%
“…Absorber material properties (e.g., absorptance, transmittance) and geometries Pakdaman et al 2011;Chabane et al 2014), number of transparent covers (glazing) (Belusko et al 2004) and geometry of air passage (Budea 2014;Forson et al 2003) greatly influence the outlet temperature in a solar air heater. Considering variations in design and location, usually 300-900 kWh of thermal energy per year can be extracted by a collector of 1 m 2 surface area (Faninger 2010).…”
Section: Conversion Efficiencymentioning
confidence: 99%
“…A single pass solar air heater is developed in (Chabane, Moummi, & Benramache, 2014) with five fins in form of semi cylindrical longitudinal under absorber plate. The collector is compared with a solar air collector without fins.…”
Section: Introductionmentioning
confidence: 99%